2001
DOI: 10.7901/2169-3358-2001-2-1269
|View full text |Cite
|
Sign up to set email alerts
|

Making, Measuring, and Using Water-Accommodated Fractions of Petroleum for Toxicity Testing

Abstract: Oil spill response can be highly affected by the perceived costs and benefits of a particular countermeasure. Responders' perceptions of these can be influenced by the means in which scientific data are collected and presented. To date, a large amount of information has been generated on the aquatic toxicity of oil, dispersants, and dispersed oil. Unfortunately, many of these data are not comparable because of differing toxicological and analytical methodologies, as well as frequent lack of analytical verifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…That these results differ somewhat may be explained by variation in exposure methods used (constant, spiked, static renewal), however, each study reported a similar toxicity for WAFs and CEWAFs based on comparison of TPHs. Similar results have been reported for Americamysis (Holmesimysis) costata (1-35 mg L´1 WAF, 8-33 mg L´1 CEWAF, 96 h) and L. setiferus juveniles (6.5 mg L´1 WAFs, 5-7.5 mg L´1 CEWAFs, 96 h) [13,25,44]. In contrast, we report a 96 h TPH toxicity with larval F. duorarum (0.029-0.037 mg L´1 WAFs, 0.27-1.38 mg L´1 CEWAFs), indicating that WAFs were more toxic.…”
Section: Survivalsupporting
confidence: 85%
“…That these results differ somewhat may be explained by variation in exposure methods used (constant, spiked, static renewal), however, each study reported a similar toxicity for WAFs and CEWAFs based on comparison of TPHs. Similar results have been reported for Americamysis (Holmesimysis) costata (1-35 mg L´1 WAF, 8-33 mg L´1 CEWAF, 96 h) and L. setiferus juveniles (6.5 mg L´1 WAFs, 5-7.5 mg L´1 CEWAFs, 96 h) [13,25,44]. In contrast, we report a 96 h TPH toxicity with larval F. duorarum (0.029-0.037 mg L´1 WAFs, 0.27-1.38 mg L´1 CEWAFs), indicating that WAFs were more toxic.…”
Section: Survivalsupporting
confidence: 85%
“…The WAF preparation is based on previous methods described in Singer et al and Barron and Ka'aihue . Low‐energy WAFs were prepared in 10‐L clear glass aspirator bottles with a bottom dispensing port.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic toxicity was measured by exposing trout embryos for 25 d, from hatch to swim-up, to chemically dispersed oil or oil fractions [16,25], with death as the only endpoint considered. Fluorescence of water samples was used to determine measured hydrocarbon concentrations, which were the basis for calculating median lethal concentrations.…”
Section: Bioassaysmentioning
confidence: 99%